Syzygium polyanthum (Wight) walp: a potential phytomedicine - Ismail, Azlini; Wan Ahmad, Wan Amir Nizam (Phcog.Net., 2019)
Ethnomedicinal plant is one of the important sources for drug discovery. Syzygium polyanthum (Wight) Walp is one of the ethnomedicinal plants that is currently gaining attention for its various pharmacological potentials. This review evaluates its traditional uses, chemical profiles, toxicological aspects, nutritional values, as well as its pharmacological properties. From our literature search in Science Direct, Scopus, and Google Scholar databases, it was found that S. polyanthum has valuable therapeutic potentials including antidiabetic, antihypertensive, antimicrobial, antioxidant, anticancer, antitumor, antidiarrheal, acetylcholinesterase inhibitory, and dental plaque inhibition properties. However, few research areas, especially its toxicological profiles, mechanism of actions, as well as identification of its bioactive compound, require more in-depth studies.